Zlom obraznih kosti z ogrožajočim podkožnim emfizemom vratu in pnevmomediastinumom - Vogelnik, Jože (Medicinski razgledi, 2010)
Traumatic pneumomediastinum is usually caused by severe thoracic injury, resulting in blunt or penetrating neck, chest or abdominal trauma. Subcutaneous emphysema of the neck and pneumomediastinum following facial trauma in the absence of neck, chest or abdominal injuries is a rare entity. There are only a few cases in the medical literature of a pneumomediastinum following isolated facial trauma. A case report of cervical subcutaneous emphysema and pneumomediastinum secondary to isolated facial trauma is presented. The anatomic mechanism of injury, diagnosis and treatment modalities are discussed.
Keywords: poškodbe; obrazne kosti; zlomi; dihalna stiska; emfizem